The 22 July 2009 Total Solar Eclipse: Modeling D Region Ionosphere Using Narrowband VLF Observations - Venkatesham, K.; Singh, Rajesh; Maurya, Ajeet K.; Dube, Adarsh; Kumar, Sushil; Phanikumar, D.V. (My University, 2019)
We present D region ionospheric response to 22 July 2009 total solar eclipse by modeling 19.8-kHz signal from NWC very low frequency (VLF) navigational transmitter located in the Australia. NWC VLF signal was received at five stations located in and around eclipse totality path in the Indian, East Asian, and Pacific regions. NWC signal great circle paths to five stations are unique having eclipse coverage from no eclipse to partiality to totality regions, and the signal is exclusively confined in the low and equatorial regions. Eclipse-induced modulations in NWC signal have been modeled by using long-wave propagation capability code to obtain D region parameters of reflection height (H0 ) and sharpness factor (β). Long-wave propagation capability modeling showed an increase in H0 of about 2.3 km near central line of totality, 3.0 km in the region near to totality fringe, and 2.4 to 3.0 km in the region under partial eclipse. Using H0 and β, Wait ionosphere electron density (Ne) profile at the daytime altitude of 75 km showed a decrease in Ne by about 58% at a station near totality central line, whereas at totality fringe and in partial eclipse region decrease in the Ne was between 63% and 71% with respect to normal time values. The eclipse associated variations in the H0 , β, and Ne are less in low-latitude region as compared to midlatitude. The study contributes to explain observations of wave-like signature in the D region during an eclipse and difference in the eclipse effect in the different latitude-longitude sectors.
Keywords: Solar eclipse; Ionosphere; VLF observation